Food for thought: Cannibalistic translation in the Lestrygonians episode of James Joyce’s Ulysses - Klitgård, Ida (Academic Quarter | Akademisk kvarter, 2011)
Ida Klitgaard’s article Food For Thought is a comparative analysis the Danish translations of James Joyce’s Ulyssesparticularly as it pertains to the significance of food, enhanced into a discussion of cannibalistic and religious metaphors. Klitgaard’s analysis shows how cultural cannibalism inevitably becomes part of such a discussion.